Policy of Kampong Improvement and Public Housing: Surabaya Colonial Period (1900—1940) - Idam Setiyawan (Universitas Gadjah Mada, 2017)
The origins of the policy of kampong improvement and public housing beginning of the 20th century and anyone who participated in it in encouraging the policy and its results originated from the poor condition of the kampong environment in the Surabaya city since the 1900s, which has caused the spread infectious diseases and casualties for the urban community and the lack of provision of adequate housing for them. Kampong and people’s housing problems developed in 1925, along with the ethical political discourse of the Indies in the early 20th century. The characters such as Tillema, Thomas Karsten, Von Vaber, Westerveld and dr Soetomo began to participate. kampong situation and lack of public housing eventually became the attention of Surabaya city government. The improvement of indigenous kampong in Krembangan and other kampong. And the construction of public housing for the community people in Sidodadi and other areas has been done and has become one of the most interesting portraits in the policy of kampong improvement and public housing in Surabaya city.